Assessment of micro and macro nutrients in poultry feeds available in Dhaka city, Bangladesh - Islam, Md Didarul; Fahmida Jannat, Ashiqur Rahaman (Journal of Scientific Agriculture, 2017)
This study was based on to determine the concentration of macro and micro nutrients as well as toxic and nontoxic heavy metals present in the chicken feed available in Dhaka city of Bangladesh. All macro nutrients, if present in the feed at high concentration have some adverse effect, at the same time if this nutrient present in the feed at low concentration this have some adverse effect too. So that this nutrient level should be maintained at a marginal level. On the other side toxic heavy metals if present in the feed at very low concentration those can contaminate the total environment of the ecosystem. In this study six brand samples (starter, grower, finisher and layer) which was collected from different renowned chicken feed formulation industry in Bangladesh. Those samples were prepared for analysis by wet-ashing and then metals were determined by Atomic Absorption Spectroscopy. It was found that 27.7 to 68.4, 57.3 to 121.9, 0.21 to 4.1, 0.32 to 2.1, 0.11 to 1.58, 0.28 to 2.11 and 0.28 to 1.78 for zinc, iron, copper, mercury, cadmium, nickel and cobalt respectively. It was found that essential macro and micro nutrients were present in the feed in low concentration on the other side mercury was present in high concentration in the feed samples